FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER CYCLICALS DI BEI - Gunawan, Audrey Adelia; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to analyze the effect of firm size, leverage, profitability, and liquidity on the firm value. This research was conducted on consumer cyclicals sector companies (non-primary consumers) listed on the Indonesia Stock Exchange from 2018 to 2021, samples were selected using the purposive sampling method based on data that matched the criteria of 54 companies. The data processing technique uses multiple regression analysis assisted by the SPSS (Statistical Product and Service Solution) for windows released 16. The results of this study show that the size of the company affects the value of the company. Meanwhile, leverage, profitability, and liquidity have no effect on the firm.